Enhancing home based care for HIV patients using an advisory expert system - Mburu, Christine Wanjiru (Department of Computer Science, 2014)
South Africa has one of the highest Human Immunodeficiency Virus (HIV) prevalence rates in the world. People living with HIV/AIDS experience many unrelieved symptoms. Nutritional care and support are important in preventing development of nutritional deficiencies. Home remedies can extend and improve the quality of their lives. Home remedies treatment involves eating healthy food, avoiding certain types of foods, psychological and emotional support and practicing hygiene to avoid skin infections (Sizani, Bandile; Nikiwe 2012). HIV/AIDS treatment and management strategies require ongoing management and support. In this research, we work with people from a clinic in Gugulethu Township in Western Cape, South Africa. The area has high prevalence of HIV (Ministry of health South Africa 2011). Most of the HIV patients in this area access medical information by walking long distances to the clinic. Most of these patients are poor and sometimes cannot afford to visit the clinic regularly for medical advice. In this township there is scarcity of health care workers (HCWs). The HCWs toil on many fronts to meet the enormous demand for the HIV/AIDS services but they are not able to meet the patients' needs. The aim of this research is to empower HIV-patients to self-manage the HIV-related symptoms which they experience. We investigated the way in which the HCWs deliver information to the patients. We interviewed the patients to understand what measures they take to manage the symptoms which they experienced. Consequently, we developed an advisory expert system to enhance Home-Based Care for HIV patients. An advisory expert system is defined as a computing system which is capable of representing and reasoning about some knowledge–rich domain, with a view to solving problems and giving advice (Gustafson et al. 1994). Since South Africa has high mobile phone penetration and most of the patients own them, we opted to use mobile phone as a tool to access the information provided by the advisory expert system. The system was then deployed at the clinic. We trained both HCWs and patients how to use the system. The findings were captured and reported after a six month deployment of the system. The results show that our system can be used as an effective tool to disseminate nutritional and psychological support information to HIV- patients in Gugulethu. The system is simple, yet practical. It helps the patients to self-manage the HIV-related symptoms which they experienced and at the same time, saves time and cost for both HCWs and the patients.